Nutritional Stress Leads to Persistence and Persister-like Growth in Staphylococcus aureus - Katie R. Risoen; Claire A. Shaw; Bart C. Weimer (Pathogens)
Staphylococcus aureus is a versatile zoonotic pathogen capable of causing a wide range of infections. Due to the organism’s ability to persist, recalcitrant and recurring infections are a major concern for public and animal health. This study investigated the establishment of persistence using two S. aureus strains—ATCC 29740, a bovine mastitis isolate, and USA300, a human clinical isolate—under substrate depletion. This nutritional stress established a persistence phenotype where the strains remained persistent for >120 days at notable concentrations [>2 log10 CFU/mL] and developed persister-like growth, including small colony variant formations. With RT-qPCR, we found the cell density was higher than represented by the plate count while the intracellular ATP remained constant during the persistence phase. These findings indicate that S. aureus has complex survival strategies to support its persistent state, providing a host-specific perspective when addressing recurrent infections in human and animal infectious diseases.